Упростите выражения:
6m-3z m+3z
--------- - ----------
а) 8m+3z m-6z

3a+d 7a+5d
--------- - ---------
б) 2a-5d a+3d

m+5y 8y-4m
---------- - -----------
в) 2y-2m m+3y

1

Ответы и объяснения

Лучший Ответ!
2013-10-23T18:46:19+04:00
А) 6m-3z / 8m+3z - m+3z / m-6z = ((6m-3z)(m-6z) - (m+3z)(8m+3z)) / (8m+3z)(m-6z)
 = (6m^2-36mz-3mz+18z^2 - 8m^2-3mz-24mz-9z^2) / (8m+3z)(m-6z) = -2m^2-66mz+9z^2 / (8m+3z)(m-6z) 
б) 3a+d / 2a-5d - 7a+5d / a+3d = ((3a+d)(a+3d) - (7a+5d)(2a-5d)) / (2a-5d)(a+3d) = 
= (3a^2+9ad+ad+3d^2-14a^2+35ad-10ad+25d^2) / (2a-5d)(a+3d) =
= -11a^2+35ad+28d^2 / (2a-5d)(a+3d)
в) m+5y / 2y-2m - 8y-4m / m+3y = ((m+5y)(m+3y) - (8y-4m)(2y-2m)) / (2y-2m)(m+3y) = 
= (m^2+3my+5my+15y^2-16y^2+16my+8my-8m^2) / (2y-2m)(m+3y) =
=  -7m^2+32my-y^2 / (2y-2m)(m+3y)